A comparison of different doses of fentanyl for patients undergoing elective colonoscopy: a randomized double-blind clinical trial - Mirza Kovačević; Adisa Šabanović Adilović; Nermina Rizvanović; Harun Adilović; Malik Ejubović; Alma Jahić Čampara (Medicinski glasnik, 2022)
Aim: To investigate analgesic and side effects of different doses of fentanyl in combination with propofol for colonoscopy. Methods: This prospective randomized double-blind study conducted between 2019 and 2020 included 64 patients. Patients were randomized: Group 1 (fentanyl 0.5 ?g/kg) and Group 2 (fentanyl 1.0 ?g/kg) both in combination with propofol. Ramsay sedation score (RSS) was obtained at 5 with an additional dose of propofol. The primary outcome was the patient’s postprocedural pain and adverse events during and after the procedure. Results: The RSS means were statistically lower for Group 2 at the beginning and every 5 minutes of the procedure. Mean arterial pressure (MAP) for Group 2 (first, 5, 25 and 30 min) was significantly lower (p=0.000, and heart rate (HR) was significantly higher for Group 1 (during the entire procedure) (p=0.000) than in another group; peripheral oxygen saturation (SpO2 ) was significantly lower for measurements within both groups (Group 1, 5, 10, 15 min; Group 2, 5, 10,15 min) (p=0.000 and p=0.000, respectively). Anxiety (p=0.010), weakness (p=0.000) and confusion (p=0.023) proved to be significantly higher for Group 1, and hypotension (p=0.001) for Group 2 than in another group. No statistical significance of Visual Analogue Pain Scale (VAS) (p=0.501) and Aldrete recovery score (ARS) (p=0.845) was found. Conclusion: There was no significance in postprocedural abdominal pain between the group of patients administered fentanyl at a dose of 0.5 ?g/kg and the group of patients administered fentanyl at a dose of 1.0 ?g/kg; however, prevalence of complications was more significant in the group with a fentanyl at a dose of 0.5 ?g/kg.
Keywords: abdominal pain; incidence; opioid